Sosialisasi Guru Madrasah dalam Meningkatkan Kedisiplinan Pelajar di Madrasah Aliyah Swasta Amaliyah Tanjung Tiga - H. M. Baihaqi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study seeks to describe the socialization of madrasah teachers in improving student discipline at the private madrasah aliyah amaliyah tanjung three. The purpose of the research is to provide information and education to readers that madrasas are educational institutions that have a strategic role to build character so that they become disciplined students. The data collection techniques used were observation and unstructured interviews and then the data were analyzed objectively and described scientifically by following the procedures for writing scientific papers. The results of the study were found as follows: First, socialization in improving student discipline was carried out in persuasive ways. Second, private madrasah aliyah teachers at tanjung three always carry out internal monitoring of student character and student discipline, if there are still undisciplined students, madrasa teachers identify early triggers for these students to become undisciplined. Third, private madrasah aliyah teachers in Tanjung Tiga always provide examples of discipline for students to be role models for them. Fourth, the head of the private madrasah aliyah tanjung three conducts periodic evaluations of all madrasah residents with the aim of improving things that must be improved for the next day. Fifth, private madrasah aliyah teachers at Tanjung Tiga on various occasions always educate students to always comply with the rules and regulations that apply in the madrasa environment.